Credit cards preferences of islamic and conventional credit card - Mohd Dali N.R.S.; Yousafzai S.; Hamid H.A. (Emerald Group Publishing Ltd., 2024)
Purpose The main aim of this paper is to identify whether certain consumers behave irrationally when it comes to select banking products. This paper builds on one of the most signifcant banking products that is the credit card. Design/methodology/approach This is an exploratory research paper. Therefore, only descriptive analysis on the differences between three credit card user groups such as the Islamic credit card users, conventional card users and users who decide to use both credit cards, conventional and Islamic, were presented. Findings The demographic and psychographic factors for the three different groups differ. In addition, there are four factors that infuence the credit card selection. The factors are insurance/takaful provided by the credit issuers, cost associated with the credit card, the reward points programme offered and the convenience factors. Furthermore, the study found that three of the factors except insurance/takaful are signifcantly different between three credit card groups. Research limitations/implications This paper is limited to the context of Malaysia and the respondents are mostly from the same ethnic. Therefore, it could not be generalised in the context of other countries and further studies comparing different culture or ethnic could beneft and enrich the topic of study. Practical implications The Islamic and conventional banks could focus on several factors infuencing customers selection and could focus to improve certain lacking areas as perceived by the consumers. The ability to increase the perceptions of the consumers regarding their credit cards will enable their products to be chosen in the market. Originality/value There was a signifcant amount of literature discussed in the Islamic banking selection factors. However, little attention being paid to the selection of a specifc banks product. This study offers a study that looks into the selection of the credit card offered by the banks in respect to the irrational behaviours of the religious consumers in economic activities as compared to the conventional economists. This paper will contribute to the body of existing literature of banking selection. Emerald Group Publishing Limited